2013
DOI: 10.1002/jcb.24547
|View full text |Cite
|
Sign up to set email alerts
|

Normal human embryonic stem cell lines were derived from microsurgical enucleated tripronuclear zygotes

Abstract: A normal fertilized human zygote contains two pronuclei, but zygotes may also display one, three, or even more pronuclei resulting from irregular insemination or meiotic division. Today diploid and triploid human embryonic stem cell (hESC) lines have been derived from tripronuclear (3PN) triploid zygotes, and an in-vitro fertilization (IVF) baby was born from a rescued diploid zygote by removing the extra male pronucleus of the 3PN zygote. However, whether hESCs can be derived from a rescued 3PN zygote is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, since all hESC lines have chromosomal abnormalities, the risks involved in this method need to be evaluated [33]. In our previous study, we also indicated that the diploid hESC lines can be derived from 3PN zygotes when one pronuclear is removed [8], and Jiang et al subsequently proved our results [9]; however, the lower efficiency limited the development of this method. Here, we have developed a new culture system to promote the application of 3PN zygotes.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…However, since all hESC lines have chromosomal abnormalities, the risks involved in this method need to be evaluated [33]. In our previous study, we also indicated that the diploid hESC lines can be derived from 3PN zygotes when one pronuclear is removed [8], and Jiang et al subsequently proved our results [9]; however, the lower efficiency limited the development of this method. Here, we have developed a new culture system to promote the application of 3PN zygotes.…”
mentioning
confidence: 59%
“…However, the lower developmental efficiency of this process limited its application in the clinical setting, and only about 10% of the repaired 3PN zygotes could develop into the blastocyst stage [8,34]. Although Jiang et al showed that 25 r2PN embryos could develop into blastocysts using this method, the fact that only 2 hESC lines were derived from 11 blastocysts indicated the lower quality of the blastocysts obtained [9].…”
Section: Fig 4 Effect Of Egf-bdnf-igf-1 Supplement On the Chromosommentioning
confidence: 99%
See 2 more Smart Citations
“…The 1PN embryos had approximately 48.7% normal diploid chromosomes (Yan et al, 2010), whereas the aneuploidy incidence in 3PN zygotes was approximately 70À80% (Staessen and Van Steirteghem, 1997). Despite these aneuploidy frequencies, hESCs derived from 0-, 1-, and 3PN zygotes can possess a normal karyotype and express typical stem-cell surface markers (Heins et al, 2004;Suss-Toby et al, 2004;Lavon et al, 2008;Chen et al, 2012a;Jiang et al, 2013). Indeed, our hESCs Zh19 and Zh20 carried normal karyotypes even though they were derived from 3PN zygotes, which are not usually regarded as suitable for continued culture in assisted-reproduction systems; how these 3PN zygotes generated hESC lines with normal karyotypes remains unclear.…”
Section: Discussionmentioning
confidence: 99%